[PP.04.33] COVARIABLES AND TYPES OF ABNORMAL LEFT VENTRICULAR GEOMETRY IN YOUNG AND MIDDLE-AGED ISCHEMIC STROKE SURVIVORS – THE NORWEGIAN STROKE IN THE YOUNG STUDY. (September 2017) - Saeed, S.; Waje-Andreasen, U.; Pristaj, N.; Oftedal, Å.; Naess, H.; Fromm, A.; Gerdts, E.
Abstract : Objective: Little is known about the prevalence and covariables of abnormal left ventricular (LV) geometry in younger ischemic stroke patients. Figure. No caption available. Design and method: We used clinical and echocardiographic data from 276 patients aged 15–60 years included in the Norwegian Stroke in the Young Study. LV hypertrophy (LVH) was defined as LV mass index >46.7 g/m 2 .7 in women and >49.2 g/m 2 .7 in men. Concentric remodeling was considered present if posterior wall thickness/LV internal diameter ratio was >/= 0.43 in the absence of LVH. Arterial damage was assessed by mean common carotid intima-media thickness (IMT) and carotid-femoral pulse wave velocity (PWV). Results: Abnormal LV geometry was found in 37% of patients. Concentric remodeling was the most common abnormal LV geometry, found in 21%, while LVH was found in 16% (Table 1). In multivariable logistic regression analyses, LVH was associated with high for age PWV, higher body mass index, creatinine, and presence of diabetes and hypertension (all p < 0.05). Concentric remodeling was associated with higher mean carotid IMT, older age and absence of obesity (all p < 0.05). Conclusions: In ischemic stroke survivors <60 years of age, abnormal LV geometry was common. Concentric remodeling was found in 21% and associated with higher age and mean carotid IMT. LVH was found in 16% and associated with higher arterial stiffness, hypertension and diabetes